Modernizing George Eliot The Writer as Artist, Intellectual, Proto-Modernist, Cultural Critic - Newton, K.M (Bloomsbury Academic, 2011)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. George Eliot's work has been subject to a wide range of critical questioning, most of which relates her substantially to a Victorian context and intellectual framework. This book examines the ways in which her work anticipates significant aspects of writing in the twentieth and indeed twenty first century in regard to both art and philosophy. This new book presents a series of linked essays exploring Eliot's credentials as a radical thinker. Opening with her relationship to the Romantic tradition, Newton goes on to discuss her reading of Darwinism, her radical critique of Victorian values and her affiliation with the modernists. The final essays discuss her work in relation to Derridean themes and to Bernard Williams' concept of moral luck. What emerges is a very different Eliot from the conservative figure portrayed in much critical literature.